2014
DOI: 10.1186/2052-336x-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Noise annoyance through railway traffic - a case study

Abstract: This paper describes an assessment of noise caused by railway traffic in a large Latin American city. Measurements were taken of noise levels generated by trains passing through residential neighborhoods with and without blowing their horns. Noise maps were also calculated showing noise pollution generated by the train traffic. In addition - annoyance of the residents - affected by railway noise, was evaluated based on interviews. The measurements indicated that the noise levels generated by the passage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Trombetta Zannin and Bunn studied noise annoyance through railway traffic in a large Latin American city. Their results revealed that railway traffic caused irritability, headaches, poor concentration, and insomnia; 88% of residents in the studied city claimed that nocturnal noise pollution is the most distressing type (22). In a survey by Lam et al, traffic noise was identified as the most annoying source of noise pollution by 60% of people living in highly noisy areas.…”
Section: Introductionmentioning
confidence: 91%
“…Trombetta Zannin and Bunn studied noise annoyance through railway traffic in a large Latin American city. Their results revealed that railway traffic caused irritability, headaches, poor concentration, and insomnia; 88% of residents in the studied city claimed that nocturnal noise pollution is the most distressing type (22). In a survey by Lam et al, traffic noise was identified as the most annoying source of noise pollution by 60% of people living in highly noisy areas.…”
Section: Introductionmentioning
confidence: 91%
“…Providing the acoustic comfort ofbuilt-up areas in urban planning is a very urgent task [20]. Scientific researches to combat noise in the urban environment have been carried out everywhere throughout the world, mainly, in the direction of assessing the acoustic impact of various modes of transport and reducing it, including studies of acoustic obstructions various types physical characteristics and development of methods for assessing their acoustic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although emissions from railway systems are far less than that of automobile vehicles, the environmental pollution from railway operations should not be underestimated. Frequently mentioned types of impact caused by rail transportation include noise (Aasvang et al, 2007;Ali, 2005;Trombetta Zannin and Bunn, 2014), vibration (Kouroussis et al, 2014;Sanayei et al, 2013) and air pollution (Dincer and Elbir, 2007;Salma et al, 2009). In contrast, there have been very few studies into the impact on water courses.…”
Section: Introductionmentioning
confidence: 92%